The Potential of Carbon-based Materials for Photocatalytic Application - Wang, Jian; Huang, Hengming; Xu, Zhongzi; Kou, Jiahui; Lu, Chunhua (Current Organic Chemistry, 2014)
Photocatalytic nanocomposites have attracted increasing attention due to their potential for solving energy and environmental problems. Carbon-based materials that are stable, highly electroconductive, and easy to be modified, are increasingly being used to form composites with semiconductors to enhance their photocatalytic activity. This review surveys recent literature and highlights the progress being made in the development of carbon-based materials for photocatalytic application, including carbon nanotubes, graphene, carbon nanodots, activated carbon, [60]-fullerene and C3N4. The synthesis methods and mechanisms for the enhancement of the photocatalytic performance are discussed, along with the challenges and opportunities for the future development of carbon-based photocatalysts.
Keywords: H2 production